The law of energy underground : understanding new developments in subsurface production, transmission, and storage - Zillman, Donald N.; McHarg, Aileen; Bradbrook, Adrian J.; Barrera-Hernâandez, Lila Katz, 1965- (Oxford : Oxford University Press, 2014)
Many developments in energy production and use involve underground resources. Fracking to capture oil and gas resources, storage of harmful carbon gases, and long-term disposal of waste have large implications for the future. This book provides a clear and insightful overview of the law and policy issues surrounding these new technologies.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 23, 2014).
Keywords: Power resources -- Law and legislation; Energy development -- Law and legislation